Set3 Is Required for Asexual Development, Aflatoxin Biosynthesis, and Fungal Virulence in Aspergillus flavus - Lan, Huahui; Wu, Lianghuan; Fan, Kun; Sun, Ruilin; Yang, Guang; Zhang, Feng; Yang, Kunlong; Lin, Xiaolu; Chen, Yanhong; Tian, Jun; Wang, Shihua (Frontiers in Microbiology, 2019)
Aspergillus flavus is an opportunistic pathogenic fungus both for plant and animal that produces carcinogenic toxins termed aflatoxins (AFs). AFs are highly detrimental to animal and human health. To identify possible genetic targets to reduce AFs contamination, in this study, we have characterized a novel A. flavus Set3, sharing sequence homology with the yeast protein Set3. The set3 deletion mutants presented no difference in growth rate but alterations in asexual development and secondary metabolism compared with the wild-type A. flavus. Specifically, deletion of set3 gene decreased conidiophores formation and conidial production through down-regulating brlA and abaA genes expression. In addition, normal levels of set3 were required for sclerotial development and expression of sclerotia-related genes nsdC and sclR. Further analyses demonstrated that Set3 negatively regulated AFs production as well as the concomitant expression of genes in the AFs gene cluster. Importantly, our results also displayed that A. flavus Set3 was involved in regulation of pathogenicity to seeds. Taking together, these results revealed that a novel Set3 played crucial roles in morphological development, secondary metabolism and pathogenicity in A. flavus.